2020
DOI: 10.3390/app10103499
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Polyphenolics in Extracts from Natural Materials on Metabolic Activity of Metastatic Melanoma WM-266-4 Cells

Abstract: The importance of natural crops in medicine and pharmacy is growing. Beside bioactive compounds used directly as therapeutic agents, there are also raw materials used for drug synthesis or as a basic model for new biologically active compounds. In this paper, the optimum conditions for material extraction of Curcuma longa, Lycium barbarum, Equisetum arvense, Vitis vinifera, and Rosmarinus officinalis were investigated to achieve high antioxidant levels. The main aim of this study was to verify the correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 95 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…It manifests very good scavenging Ginger (Zingiber officinale) is a member of the plant family that includes cardamom and turmeric. In previous studies [40], we investigated turmeric and demonstrated that it is a strong source of antioxidants and that turmeric extract has a significant effect on the metabolic activity of melanoma cells (WM-266-4), even at the lowest extract concentration of 0.001 mg/mL [36]. According to recent studies, ginger also has antioxidant [12,13,41,42], anti-microbial [43], anti-cancer and anti-inflammatory activity.…”
Section: Introductionmentioning
confidence: 99%
“…It manifests very good scavenging Ginger (Zingiber officinale) is a member of the plant family that includes cardamom and turmeric. In previous studies [40], we investigated turmeric and demonstrated that it is a strong source of antioxidants and that turmeric extract has a significant effect on the metabolic activity of melanoma cells (WM-266-4), even at the lowest extract concentration of 0.001 mg/mL [36]. According to recent studies, ginger also has antioxidant [12,13,41,42], anti-microbial [43], anti-cancer and anti-inflammatory activity.…”
Section: Introductionmentioning
confidence: 99%